Mechanical Attributes of Uniaxial Compression for Calcium Carbonate Whisker Reinforced Oil Well Cement Pastes. (23rd November 2017) - Yang, Yuanyi; Fu, Shun; Li, Xingkui
Abstract : It is crucial for design and safety of the cementing sheath to develop better understanding of the CaCO3 whisker reinforced oil well cement pastes. The uniaxial compression curve, mechanical constitutive relation, and reinforcing mechanism of the CaCO3 whisker reinforced oil well cement pastes are studied in this script. The results indicate that the CaCO3 whisker under the 10% dosage could improve the tensile strength of the cement paste significantly. The peak stress, elasticity modulus, and the energy at different stages of the stress-strain curve of the CaCO3 whisker reinforced cement paste are reinforced with the increasing of CaCO3 whisker. Afterward, the constitutive model of stress-strain curve, the toughness index, and capability coefficients index of the CaCO3 whisker reinforced cement paste are established. A physical model of the interface layer is also established and the micromechanical reinforcement is related to the double film layer between the CaCO3 whisker and cement matrix which could be bonded with much more fastness to the cement surface. The development of this script provides new ways to analyze the toughening mechanism of CaCO3 whisker and establishes a correlation between basic material structure and the physical properties.